Historical-conceptual overview of the Law and Literature Movement in the Anglo-Saxon World - Mejía Hernández, Diana O. (2023)
The present investigation carries out a historical and conceptual review of the Law and Literature Movement in its AngloSaxon origins. For this, the main contributions of the representatives who appeared as central figures are enunciated and described, as well as the pioneering works that stood out in the three great moments of said studies, from the first inquiries to the theoretical proposals developed within the European universities and AngloAmerican. On the other hand, it explores the academic debate that took place around the relations between law and literature during the second half of the 20th century and examines the central aspects of the primary intersections known as: Law in Literature, Law as Literature and Law of Literature.